2021
DOI: 10.1002/advs.202102128
|View full text |Cite
|
Sign up to set email alerts
|

Optical Inspection of 2D Materials: From Mechanical Exfoliation to Wafer‐Scale Growth and Beyond

Abstract: Optical inspection is a rapid and non-destructive method for characterizing the properties of two-dimensional (2D) materials. With the aid of optical inspection, in situ and scalable monitoring of the properties of 2D materials can be implemented industrially to advance the development and progress of 2D material-based devices toward mass production. This review discusses the optical inspection techniques that are available to characterize various 2D materials, including graphene, transition metal dichalcogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 262 publications
(594 reference statements)
0
9
0
Order By: Relevance
“…Interestingly, this shift of the Raman peaks is not or barely discussed in works related to strained or vertical heterostructures built from transferred TMDs. ,,, More recent works, however, exhibit a phonon hardening of all Raman modes for MoS 2 and WSe 2 when subjected to high pressures. , In 2016, M. S. Kim et al, when studying dry transferred TMDs, observed some small Raman shifts of the first order bands and related them to electron doping in MoS 2 and hole doping in MoSe 2 resulting from charge transfer. Nevertheless, when MoS 2 is submitted to electron gate doping, one observes that there is a downshift of the out-of-plane A′ 1 mode, together with an increase of its fwhm, while the E′ mode does not change, which is explained because of the weaker electron–phonon coupling of the in-plane mode. When the gate voltage is tuned to induce a hole doping, there are no observable changes in the Raman modes at all. The same behavior was observed for other mono- and bilayer TMDs, including MoSe 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this shift of the Raman peaks is not or barely discussed in works related to strained or vertical heterostructures built from transferred TMDs. ,,, More recent works, however, exhibit a phonon hardening of all Raman modes for MoS 2 and WSe 2 when subjected to high pressures. , In 2016, M. S. Kim et al, when studying dry transferred TMDs, observed some small Raman shifts of the first order bands and related them to electron doping in MoS 2 and hole doping in MoSe 2 resulting from charge transfer. Nevertheless, when MoS 2 is submitted to electron gate doping, one observes that there is a downshift of the out-of-plane A′ 1 mode, together with an increase of its fwhm, while the E′ mode does not change, which is explained because of the weaker electron–phonon coupling of the in-plane mode. When the gate voltage is tuned to induce a hole doping, there are no observable changes in the Raman modes at all. The same behavior was observed for other mono- and bilayer TMDs, including MoSe 2 .…”
Section: Discussionmentioning
confidence: 99%
“…2D materials have been investigated widely using standard optical spectroscopy, spectroscopic ellipsometry, Raman spectroscopy, and photoluminescence spectroscopy. They are also frequently characterized using time-resolved PL, pump–probe spectroscopy, Fourier transform infrared (FTIR) spectroscopy, and X-ray scattering, diffraction, and reflectivity . These characterization techniques are used for various purposes: to locate the grown 2D materials, to investigate defects in the structure, to probe strain in the structure, to detect the concentration and nature of dopants in the structure, to study carrier dynamics, to identify polaritons or functional groups in 2D materials, to probe lattice spacings, to observe the van der Waals integration, and so on .…”
Section: Incorporation Of Characterization and Metrology Unitsmentioning
confidence: 99%
“…Additionally, optical anisotropy can be correlated to the intensity ratio of Raman D and G bands in graphene . Although used primarily for graphene, spectroscopic ellipsometry provides more reproducible data with higher resolution than optical spectroscopy by measuring the amplitude ratio of reflected light rather than the absolute intensities of reflected and transmitted light …”
Section: Incorporation Of Characterization and Metrology Unitsmentioning
confidence: 99%
See 2 more Smart Citations